Transformation of Texts as Expressive Spaces in Classic Malay Literary Works: Learning to Write Poems in Philology Courses - Adriansyah Adriansyah; Elmustian Elmustian; Mangatur Sinaga; M. Firdaus (STAI Hubbulwathan Duri, 2024)
This study investigates the transformation of poems into expressive spaces in philology learning, aiming to foster active and creative student engagement with classical Malay literature. It seeks to develop innovative teaching approaches that enhance appreciation and critical engagement. A sample of 52 students was purposively selected using the Slovin formula with a 10% margin of error. Data were collected through classroom observations, questionnaires, in-depth interviews, and document analysis of poem learning. Thematic analysis was employed to identify key patterns and themes from the data. The findings reveal that integrating poems into philology learning enhances students’ understanding and appreciation of classical Malay literature. It also boosts creativity and critical thinking, with respondents reporting an improved ability to appreciate cultural heritage and refine expressive and analytical skills. These results highlight the potential of interactive and creative methods in philology education, demonstrating their effectiveness in making classical literature more relevant and engaging for students. The study underscores the value of incorporating expressive and interactive strategies into the philology curriculum to deepen student engagement and promote a lasting appreciation of classical literature and culture.